The image of Breslau in a play "Mock. Czarna burleska" - Woźniak, Małgorzata (To Tell the History: Polish Contemporary Dramaturgy after 2006, 2023)
Mock. Czarna burleska is a musical play that premiered in 2019, in Musical Theatre Capitol in Wrocław. It is based on seven crime stories by Marek Krajewski. The author of this article claims that (apart from a policeman Eberhard Mock) the second main character of the performance is the city of Breslau. The director of this play Konrad Imiela, who wrote the songs with Roman Kołakowski as well, relying on a literature source, draws an image of a city of depravity on stage. Prostitutes are the narrators of the whole spectacle while the titular character lives in the criminal underworld of Breslau in the 20s and 30s of the twentieth century.Literary fragments that the play was based upon were used in the analysis. Detailed description of the architecture and atmosphere of the city is visible in Krajewski's writing as well. The vibe certainly arises from the genre that the author has chosen. Events of the series take place mostly in the dark streets and sinister bars, while the characters are mostly criminals. The authors of the play in question use not only a text in the case of building a certain climate but also interesting mockumentary techniques, which are a part of a wider reflection on fiction and reality. Pictures used as a part of a scenic design, as well as an exhibition in a foyer, are a mixture of photographs that are styled to look like they were made at the beginning of the twentieth century and those that are authentic. That collection is supplemented with a description, which allows the audience to dive even deeper into a narrated story.